Retrospective study of the prevalence and characteristics of adverse drug events in adults who present to an Australian emergency department. (1st January 2022) - Brown, Nathan J; Doran, Elizabeth; Greenslade, Jaimi H; Lukin, Bill; Cottrell, Neil; Jaramillo, Fabian; Coombes, Ian; Donovan, Peter; Cullen, Louise
Abstract: Objective: To determine the burden, on the ED, of harm from unintentional adverse drug events (ADEs) in the community. Methods: A retrospective, observational study of 936 randomly selected presentations to a level 6 ED at a principal referral hospital in Brisbane, Australia, in November 2017. Clinical records were screened by a pharmacist, who identified suspected ADEs. All suspected ADEs and a random selection of presentations without ADEs were reviewed by an expert panel, which classified, by consensus: occurrence and type of ADE, contribution of ADE to presentation, severity of harm and preventability of presentation. Medication‐related ED presentations (ADE‐Ps) and potential ADEs were, respectively, defined as presentations directly attributable to an ADE, and medication events that occurred but did not cause the ED presentation. Descriptive data analysis was performed. Results: The median (interquartile range) age of patients was 40 (27–58) years, with 49.7% (95% confidence interval [CI] 46.5–52.9) being male. The prevalences of ADE‐Ps and potential ADEs were 9.2% (95% CI 7.5–11.3) and 5.0% (95% CI 3.8–6.6), respectively. The severity of harm was classified as 'death or likely permanent harm' in 4.7% (95% CI 0.2–9.1) of ADE‐Ps, 'temporary harm' (89.5%, 95% CI 83.1–96.0) and 'minimal or no harm' (5.8%, 95% CI 0.9–10.8). Most (79.1%, 95% CI 70.5–87.7) ADE‐Ps were preventable. Conclusions: There is a high burden on emergency care because of unintended medication harm in the community. Interventions to reduce such harm are likely to require a co‐ordinated primary, acute and public healthcare response. The high proportion of presentations with potential ADEs indicates opportunity for harm mitigation in the ED. Abstract : In a retrospective, observational study of randomly selected ED presentations, we used a two‐stage process to review presentations for the presence of adverse drug events (ADEs). We found that 9.2% of patients had an ADE that caused the presentation, and an additional 5.0% of patients had a potential ADE (evidence of a medication error that had not yet caused harm). Unintended medication harm in the community represents a high burden to the ED.